Da’wah Radio and the Formation of Social Relations: A Communication Sociology Analysis at Radio An-Nashihah - Haeruddin; St. Magfirah Nasir; Abustani Ilyas; Asni Djamereng; Noviatin Binti Syarifuddin; Irnawati (Palakka : Media and Islamic Communication, 2026)
The purpose of this research is to analyze the role of religious broadcasting radio in shaping socio-religious relations thru the communication process between the broadcaster and the listeners. Radio An-Nashihah Sakinah with Sunnah was chosen as the research object because it consistently promotes the value of silaturahim in its broadcasting strategy. This research uses a qualitative-descriptive approach with library study and observation methods on the broadcasting programs of Radio An-Nashihah. The observations were conducted in real time during broadcasts over a two-month period, focusing on the interactions between the host, guests, and listeners in programs on religious counseling, family issues, and Quranic recitation. The analysis is conducted using a communication sociology perspective to see how the value of silaturahim is practiced in da'wah communication interactions thru radio media. The research results show that Radio An-Nashihah implements the value of silaturahim thru program planning oriented toward audience needs, human resource management according to competence, and the presentation of interactive programs such as religious consultations, family studies, and Quranic learning. The dialogical and participatory communication pattern allows for emotional closeness between the broadcaster and the listeners, thereby forming social relationships that are spiritual and communal in nature. Thus, radio not only functions as a medium for conveying religious information but also as a space for social communication that strengthens Islamic brotherhood within the community. This research shows that radio media can be an effective means of preaching in building social relations based on Islamic values in the digital communication era.